The EU after Brexit: Renewed debate about enlargement and deepening - Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2021)
The departure of the United Kingdom and the prospect of an independent Scotland seeking membership raise fundamental questions concerning the European Union's future size, geography and polity. Germany's policy on Europe is traditionally guided by the idea that enlargement and deepening are two sides of the same coin. In reality progress on integration has never matched the pace of (eastern) enlargement. The road to the 2009 Lisbon Treaty was rough, and the spectre of failure haunts any discussion of deeper reforms, especially those requiring changes to the treaties by unanimity. The Scottish question has the potential to energise enlargement policy and spur internal reforms - to prepare not just for a new 28th member, but for an EU-34.
Keywords: 320